ANALYSIS OF THE IMPLEMENTATION OF THE SIMPLE SALARY SIM APPLICATION IN GROGOL DISTRICT, SUKOHARJO DISTRICT - Efendi, Tino Feri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Abstract : Implementation of Civil Servant Salary SIM in the Administrative Service Office of the Education Unit, Grogol District, Sukoharjo Regency. This research is conducted in this analysis which contains the use of the Government Salary SIM application which is implemented in all regions as a means of calculating, storing and maintaining civil servants' data based on computerization and connected to the government-owned Internet network. The research method used was interview, application observation and literature study. The system design that can be concluded by the author is using Context Diagram, DAD, HIPO and input and output system design. Keywords : Information System, Education Office, Employees and Salaries.